Higroma carpal em ovino - Relato de caso - Góss, Geórgia Camargo; Duarte, Cláudia Acosta; Leite, Carla Teixeira [UNESP]; Cogo, Aline Bassin; Pereira, Elton Peres; Döwich, Gabriela; Da Rosa, Loreane Rosa (My University, 2016)
The carpal hygroma is characterized by an abnormal fluid accumulation in a dorsal surface of this region, that is presented with soft consistency, painless and doesn't lead to lameness. The main cause of hygroma is a constant local trauma. This is a commom disease in horses who live in hard surface sites and, it can also affect ruminants. The diagnosis is achieved by clinical signs and additional tests such as cytological analysis, radiographic and sonographic. The early diagnosis is important because the therapeutic options vary with the degree of evolution of the disease. The treatment may vary from hygroma drainage, with or without application of corticosteroids, followed by compressive bandages to the surgical ablation of this. The objective of this case report is to account the occurrence of a carpal hygroma in sheep. This report is important because the sheeps are being widely created in intensive systems and diseases like hygroma are becoming common, because this is a fundamental supply subsidy to the clinicians, in the literature, to assist in their daily routine.
Carpal hygroma in one sheep - Case report
Keywords: Carpal; Hygroma; Sheep; Surgery